RETRACTED: Peg-Asparaginase-Associated Pancreatitis in Chemotherapy-Treated Pediatric Patients: A 5-Year Retrospective Study - Zhang, Yun-yu; Yang, Qiu-shi; Qing, Xia; Li, Bi-ru; Qian, Juan; Wang, Ying; Ning, Bo-tao (Frontiers in Oncology, 2020)
Asparaginase-associated pancreatitis（AAP）is one of the most common complication in asparaginase treated ALL (Acute lymphoblastic leukemia) patients. Peg-asparaginase (Peg-asp), a chemically recombined asparaginase with lower hyposensitivity and better patient tolerance, is now approved as the first line asparaginase formulation in ALL. Peg-asp associated pancreatitis diagnosed within a 5 year-period (July 2014 to July 2019) were identified and retrospectively studied.AAP were further classified into mild/moderate and severe based on criteria in previous studies. 38 patients were enrolled in this study. Underlying disease include ALL(n=35) and lymphoma (n=3). Majority of AAP took place in first remission-induction stage (n=26, 68.4%), after a median of 2 peg-asp doses (range: 1-11). DVLP regimen (n=23) is the most prevalent peg-asp included regimen in AAP patients. Abdominal pain occurred as onset symptom after a median of 14.5 days (range:1-50) from last peg-asp administration, accompany with abdominal distension(n=14), nausea(n=17), vomiting(n=21) and febrile(n=19). Serum amylase elevation was recorded in all AAP patients, in which 65.8% patients (n=25) experienced an elevation three times above the upper normal level, fulling the Atlanta criteria. Serum lipase (median days of elevation=23days, range:4-75) is significantly elevated compared to serum amylase (median days of elevation =9 days, range:2-71) and persists at a markedly high level after serum amylase normalized. Common local complications include abdominal ascites(n=10) and peripancreatic fluid collection(n=8). 42.1% (n=16) patients classified as severe AAP had experienced systemic complication (septic shock or hypovolemic shock) or severe local complication (pseudocyst), in which 5 patients failed to recover. 84.8% (n=28/33) of the remaining patients resume chemotherapy, in which 30.3% (n=10/33) patients had their peg-asp formulation adjusted and 39.4% (n=13/33) were permanently discontinued from asparaginase. 5 patients experienced a relapse of AAP in later asparaginase administration. Comparison between mild/moderate and severe AAP patients showed a statistically significant difference in number of PICU stay (p=0.047), survival rate (p=0.009), AAP prognosis (p=0.047) and impacts on chemotherapy (p=0.024), revealing a better clinical outcome in mild/moderate AAP patients. Our study could serve as clinical evidences for future large cohort studies and pediatric AAP definition.